Segment-based Volatile Organic Compound Emission Characteristics from Different Types of Coking Plants in China - Rumei Li; Yulong Yan; Lin Peng; Yinghui Li; Zhuocheng Liu; Zhanchun Fan; Huanfeng Li; Yang Xu; Cheng Wang; Dongmei Hu; Zhiyong Li (Aerosol and Air Quality Research)
Abstract The source profiles, emission factors, and chemical reactivity of volatile organic compounds (VOCs) generated by two typical coking plants, one employing a non-recovery process and the other, a mechanical process, in Shanxi Province, a major coking hub in China, were determined for different segments of coke production during normal operations. The primary components in the stack flue gas were ethylene, 1-butene, benzene, acetylene, and 2,2-dimethylbutane for the non-recovery plant and styrene, benzene, and ethylene for the mechanical plant. The fugitive emissions were also monitored at the mechanical plant, and the most abundant species leaking from the oven were benzene, toluene, ethane, m-xylene, and ethylene, whereas those leaking from byproducts were benzene, propane, ethane, ethylene, n-pentane, n-butane, isobutene, 1-butene, toluene, and propylene. The stack flue gas at the non-recovery and mechanical coking plants exhibited VOC emission factors of 96 g Mg−1-coke and 0.4 g Mg−1-coke, respectively; thus, VOCs released by the former merit greater concern. Since the highest ozone formation potential (OFP) was observed for the stack flue gas at the non-recovery plant (80.26 mg m−3), followed by fugitive oven emissions at the mechanical plant (7.22 mg m−3), controlling these VOCs will significantly reduce their conversion into ozone. Overall, replacing non-recovery coking plants with mechanical coking plants will decrease VOC emissions and improve the ambient air quality in China.